Pring Goprak Bung Mecungul dalam Jama’ah LDII: Terminologi, Filosofi, dan Implikasinya terhadap Pendidikan di Indonesia - Sulthonul Khakim, Yunus (Paedagogie: Jurnal Pendidikan dan Studi Islam, 2026)
This study aims to analyze the meaning, philosophy, and implications of the terminology pring goprak bung mecungul in the context of Jama’ah LDII education and its relevance to the development of education in Indonesia. This study focuses on: (1) the meaning and philosophy of education contained in the terminology pring goprak bung mecungul, (2) five elements as the key to implementing the terminology pring goprak bung mecungul in Jama’ah LDII educational practices, and (3) its implications for the development of education in Indonesia. This study uses a qualitative approach guided by historical methods, such as heuristics, verification, interpretation, and historiography. Data collection techniques include document studies, observation, and in-depth interviews. This study was conducted in the Kediri and Kertosono areas, East Java, involving 12 informants consisting of LDII administrators, parents, educational experts, and members of the congregation as representatives of the five elements of development. The results of the study indicate that the terminology pring goprak bung mecungul represents a framework of character education values ​​that are realized through a program of forming 29 noble characters and implemented systematically through five elements of development as the key to the successful application of the terminology. The implementation of this terminology in formal and non-formal education of the LDII Congregation shows a significant contribution to strengthening character, increasing learning awareness, forming inherent educational awareness, and internalizing moral values. This study concludes that the terminology pring goprak bung mecungul not only functions as a cultural-religious term, but can also be developed as an alternative conceptual framework in the development of character education in Indonesia that is oriented towards the formation of personality, moral awareness, and awareness of sustainable education.